Comparison of ECHAM6-wiso near-surface water vapour isotopic composition with in situ measurements at Neumayer Station III - Werner, Martin; Bagheri Dastgerdi, Saeid; Cauquoin, Alexandre (Frontiers in Earth Science, 2025)
Water isotope records from polar ice cores are crucial proxies for reconstructing past Antarctic climate and temperature changes. For such task, a robust understanding and accurate quantification of the temporal changes between δ18O and temperature is necessary. One option to facilitate this is employing simulations from atmospheric general circulation models that incorporate stable water isotopes. In this context, we assess in this study the results of the isotope-enabled AGCM ECHAM6-wiso model. We analyse results from a high-resolution simulation covering the period 2017–2020, where the atmospheric dynamics is nudged to ERA5 reanalysis data from the European Centre for Medium-Range Weather Forecasts (ECMWF). Our investigation evaluates the agreement between different observed and simulated key physical and isotope quantities, including temperature, humidity, and the isotopic composition of surface water vapour (δ18Ov and δDv), at Neumayer Station III in East Antarctica. Additionally, our study evaluates the skill of the ECHAM6-wiso model in simulating stable water isotope ratios in snow (δ18Osnow and δDsnow) at Neumayer Station III for the recent past. The ECHAM6-wiso model exhibits skill in replicating the daily, monthly, and seasonal fluctuations of temperature, humidity, surface water vapour δ18Ov, and δDv. However, it demonstrates limitations in accurately simulating d-excess values on the different time scales. While the model does not precisely reproduce the observed surface δ18Ov-temperature relationship on a daily scale, it closely approximates this relationship on a monthly scale. For snow, the model slightly underestimates the δ18Osnow-temperature relationship when compared to observational data. To test if the ECHAM6-wiso model correctly simulates the water vapour sources and transport pathways to Neumayer Station III, we have performed related back trajectory studies. Based on simulation results of the FLEXPART model, we find that the water vapour back-trajectory results with ECHAM6-wiso are consistent with those based on ERA5 data. This result leads to the conclusion that ECHAM6-wiso is a very useful tool for analysing atmospheric moisture sources and transport pathways to East Antarctica under present climate conditions.